Visual tracking manipulator with redundancy and its application to robotic wheel assembly - Cho, C.-H.; Kang, S.; Kim, M.; Song, J.-B.; Min, S.; Kim, J.; Shin, H. (Proceedings 2001 IEEE/RSJ International Conference on Intelligent Robots and Systems. Expanding the Societal Role of Robotics in the the Next Millennium, 2001)
In this paper, a new wheel assembly automation system is proposed which assembles a wheel into a hub on a car body on a moving hanger in the car manufacturing line. A vision system is used to track the position of the hub on the moving hanger. A macro-micro structure is applied to increase a system bandwidth and accuracy to meet an insertion tolerance. The redundancy problem is solved without complicated calculations by assigning different functions that the macro manipulator tracks a velocity error and the micro regulates the position error. Experimental results show that the proposed system can be applied to the wheel assembly task on a moving hanger in the car manufacturing line.